Depression and post-traumatic stress disorder after perinatal loss in fathers: A systematic review. Issue 1 (28th October 2022) - Lamon, Lieselotte; De Hert, Marc; Detraux, Johan; Hompes, Titia
Abstract: Background: Research indicates that perinatal loss can cause profound psychological consequences in parents. However, a comprehensive summary of existing quantitative literature describing the association between perinatal loss and the development of depression/depressive symptoms or post-traumatic stress disorder (PTSD)/post-traumatic stress (PTS) symptoms in fathers has not been published. Methods: A systematic literature search (from inception to December 2021), using the PubMed, EMBASE, and Web of Science databases to articles assessing depressive or PTS symptoms, was conducted following the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines. Only studies investigating the period of intrauterine death from 20 weeks of gestation, stillbirth, or neonatal death within the first month after birth were included. Results: A final sample of 13 articles were eligible for inclusion. Some studies showed an increased risk of depressive and PTS symptoms in fathers after perinatal loss. However, many study results did not show significant differences, symptoms generally decreased over time, and the majority of studies showed higher levels of depressive and PTS symptoms in mothers, compared with fathers. Conclusions: Although the majority of the included studies showed elevated levels of depressive and/or PTSD symptoms after perinatal loss in fathers, no clear firm conclusion can be drawn, as the included studies were very heterogeneous. More homogeneous research measuring depressive and PTS symptoms in fathers is needed at the time of the loss, as the current literature available shows several limitations and gaps.